MXene coated PDA / Cu NPs composite material and preparation method thereof
By coating polydopamine on the surface of MXene and introducing "-NH" functional groups, MXene@PDA/Cu NPs composite material was prepared, which solved the problem of reduced stability caused by agglomeration during catalytic AP thermal decomposition, and achieved better catalytic effect and stability.
Patent Information
- Application Number
- CN202311320756.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
AI Technical Summary
During the catalytic thermal decomposition of ammonium perchlorate (AP), nanocopper powder is prone to agglomeration due to its small particle size and many unsaturated atoms on the surface coordination, resulting in a decrease in stability and affecting catalytic performance.
The MXene@PDA/Cu NPs composite material was used as a catalyst to coat polydopamine (PDA) on the surface of MXene and introduce "-NH" functional groups on its surface, increase the metal anchor positioning point, reduce the size of copper nanoparticles, enhance the charge transfer ability of the catalyst, and prepare the composite material by low-temperature in-situ reduction method.
The agglomeration problem of nanocopper powder in the catalytic AP process was significantly improved, the stability and catalytic effect of the catalyst were improved, and the thermal decomposition temperature of AP was reduced by 108.4℃, which was better than the catalytic effects of MXene, Cu NPs and MXene/Cu NPs.
Smart Images

Figure CN119819303A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic composite materials and relates to a MXene@PDA / Cu NPs composite material and a preparation method thereof. Background Art
[0002] Nano copper powder (Cu NPs) is one of the ideal materials for catalyzing ammonium perchlorate (AP) due to its low cost and variable valence state, and its catalytic performance comparable to that of precious metals. However, due to the small size of nano-scale copper particles and the large number of unsaturated atoms on the surface, it is easy to agglomerate to form secondary particles, which reduces its stability and thus affects its good catalytic performance.
[0003] MXene is a good dispersion carrier because of its large specific surface area and the presence of a large number of -OH, -F, -O and other end groups on its surface, so it has good adsorption capacity, electrical conductivity, thermal conductivity and in-situ initiation.
[0004] Polydopamine (PDA) contains abundant functional groups (such as catechol, quinone, and amine), exhibits high affinity to metal ions, and can form metal-organic complexes.
[0005] Chinese patent CN115093435A discloses a copper complex and its preparation method and application. 2,4-dihydroxybenzoic acid (β-Cu), divalent copper salt and o-phenanthroline are used as raw materials. In a mixed solution of water and ethanol, the pH value is adjusted with potassium hydroxide or sodium hydroxide solution, and then heated and stirred for reaction. The copper complex is filtered, washed and dried to obtain the copper complex. After adding the copper complex, its two independent exothermic processes are merged into one stage, and the peak temperature of the exothermic stage is only 52.6°C lower than the peak temperature of the high temperature decomposition stage of pure AP. A large amount of organic chemical reagents are used in the preparation process of this method, and the prepared copper complex has poor dispersion effect and poor effect on catalytic AP. Chinese patent CN104610042A discloses a method for preparing nano 2,4-dihydroxybenzoic acid (β-Cu), and nano β-Cu powder with good dispersion is obtained by wet mechanical grinding and vacuum freeze drying. The equipment used in this method is relatively complex, and the prepared nano-β-Cu powder has a large particle size of about 100 nm, which only reduces the thermal decomposition temperature of catalytic AP by about 100°C. Summary of the invention
[0006] The object of the present invention is to provide a MXene@PDA / Cu NPs composite material and a preparation method thereof.
[0007] The technical solution for achieving the purpose of the present invention is as follows:
[0008] The preparation method of MXene@PDA / Cu NPs composite material comprises the following steps:
[0009] Step 1, preparing few-layer MXene: placing MAX (Ti3AlC2) material in LiF HCl solution, stirring and etching, washing, centrifuging, peeling, and freeze-drying to obtain a two-dimensional layered material few-layer MXene;
[0010] Step 2, preparation of MXene@PDA: a few layers of MXene are dispersed in Tris-HCl buffer, dopamine hydrochloride is then added, stirred to cause polymerization, washed, and dried to obtain MXene@PDA;
[0011] Step 3, preparation of MXene@PDA / Cu NPs: adding MXene@PDA to water for ultrasonic dispersion, then adding copper nitrate, sodium hydroxide and ascorbic acid solution, and reducing the reaction at 50-60°C. After the reaction, the reaction product is cooled, filtered and washed to obtain a MXene@PDA / Cu NPs composite material with a mass ratio of MXene to Cu NPs of 50:50 to 30:70.
[0012] Preferably, in step 1, the concentration of the HCl solution is 9 mol·L -1 ; In the LiF HCl solution, the concentration of LiF is 3 mol·L -1 .
[0013] Preferably, in step 1, the etching time is 24 h, the etching temperature is 45° C., and the stirring speed is 400 rpm.
[0014] Preferably, in step 1, the washing method is to first use 2 mol·L -1 After washing with HCl solution, the samples were washed with water and ethanol for 3 times respectively. The pH of the supernatant after washing was ≥7.
[0015] Preferably, in step 1, the stripping time is 3 hours, the centrifugal speed is 3500 rpm, and the centrifugal time is 60 minutes.
[0016] Preferably, in step 2, the mass ratio of the few-layer MXene to dopamine hydrochloride is 100:10, the pH of the Tris-HCl buffer is 8.5, and the polymerization reaction time is 8 hours.
[0017] Preferably, in step 3, the molar ratio of copper nitrate to sodium hydroxide is 1:2.
[0018] Preferably, in step 3, the reaction time is 4 h.
[0019] The present invention also provides a MXene@PDA / Cu NPs composite material prepared by the above preparation method.
[0020] Furthermore, the present invention provides an application of the above MXene@PDA / Cu NPs composite material in catalyzing the thermal decomposition of ammonium perchlorate.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention adopts a low-temperature in-situ reduction method, which has a simple preparation process, mild conditions, and does not require the use of a large amount of organic chemical reagents. It has the advantages of being green and environmentally friendly, and the raw materials used are simple and easy to obtain, which is convenient for large-scale production.
[0023] (2) The present invention uses a few-layer MXene as a carrier and coats a layer of PDA on the surface of MXene, introducing "-NH" on the surface of MXene, increasing the metal anchoring sites, reducing the size of copper nanoparticles, and increasing the charge transfer capacity of the catalyst; at the same time, the addition of PDA strengthens the interaction between copper nanoparticles and the MXene carrier, inhibits the agglomeration and loss of copper nanoparticles during the reaction, thereby fixing metal or metal oxide nanoparticles on the surface of MXene, greatly improving the agglomeration problem of nano copper powder in the catalytic AP process.
[0024] (3) When the MXene@PDA / Cu NPs composite material prepared in the present invention is used as a catalyst to catalyze the thermal decomposition of AP, the thermal decomposition temperature of AP is reduced by 108.4°C. Compared with the thermal decomposition temperatures of AP catalyzed by MXene, Cu NPs and MXene / Cu NPs, the thermal decomposition temperatures are advanced by 86.8°C, 37.3°C and 4.1°C, respectively, showing a better catalytic effect on AP. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Transmission electron microscopy images of MXene material (a) and MXene@PDA / Cu NPs (50:50) composite material (b) prepared in Example 1.
[0026] Figure 2 XRD curves of Cu NPs, MXene materials, and MXene@PDA / Cu NPs of different ratios prepared in Examples 1 to 2 and Comparative Examples 1 to 3.
[0027] Figure 3 Thermal decomposition curves of ammonium perchlorate catalyzed by MXene@PDA / Cu NPs samples prepared with different mass ratios of MXene to Cu NPs.
[0028] Figure 4 Thermal decomposition curves of ammonium perchlorate catalyzed by MXene@PDA / Cu NPs samples prepared at different reduction temperatures. DETAILED DESCRIPTION
[0029] The present invention will be further described and illustrated below in conjunction with the embodiments and drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the protection scope of the present invention.
[0030] Example 1: Preparation of MXene@PDA / Cu NPs (50:50) composite material
[0031] (1) 1 g of MAX (Ti3AlC2) material was slowly added into a solution containing 1.6 g of LiF and 20 mL of hydrochloric acid (9 mol·L -1 ) in a mixed solution. Stir and etch at 45°C for 24 hours. After etching, filter and place in 30mL of dilute hydrochloric acid solution (2mol·L -1 ) acid wash for 2 h. Then wash with water and ethanol three times each until the pH of the supernatant is ≥7, and place the centrifuged product in an ice-water bath for 3 h of ultrasonication. Finally, centrifuge the solution at 3500 rpm for 60 min. Collect the upper dark green dispersion and freeze-dry to obtain the two-dimensional layered material few-layer MXene.
[0032] (2) Weigh 100 mg of a few-layer MXene and disperse it in 100 mL of tris(hydroxymethyl)aminomethane buffer (Tris-HCl, pH=8.5). Then, weigh 10 mg of dopamine hydrochloride and add it to the above suspension and stir for 8 hours to obtain self-polymerized PDA on the MXene surface. Finally, a black precipitate product was obtained by differential centrifugation (8000 rpm, 10 min), and after multiple washings with deionized water and ethanol, a black solid MXene@PDA was obtained by vacuum freeze drying for 24 hours.
[0033] (3) 100 mg of MXene@PDA was dispersed in 40 mL of deionized water. Then, 10 mL (0.157 mol / L) of copper nitrate and 10 mL (0.314 mol / L) of solution (the molar ratio of copper nitrate to sodium hydroxide was 1:2) and 6 mmol of reducing agent (ascorbic acid) were slowly added to the above system in a constant temperature water bath at 60 °C for reduction reaction. Finally, the reaction product was cooled, filtered, and washed to obtain the MXene@PDA / Cu NPs composite material.
[0034] Example 2: Preparation of MXene@PDA / Cu NPs (30:70) composite material
[0035] This embodiment is substantially the same as embodiment 1, except that the mass ratio of MXene to Cu NPs is 30:70.
[0036] Comparative Example 1: Preparation of MXene@PDA / Cu NPs (10:90) composite material
[0037] This comparative example is basically the same as Example 1, except that the mass ratio of MXene to Cu NPs is 10:90.
[0038] Comparative Example 2: Preparation of MXene@PDA / Cu NPs (70:30) composite material
[0039] This comparative example is basically the same as Example 1, except that the mass ratio of MXene to Cu NPs is 70:30.
[0040] Comparative Example 3: Preparation of MXene@PDA / Cu NPs (90:10) composite material
[0041] This comparative example is basically the same as Example 1, except that the mass ratio of MXene to Cu NPs is 90:10.
[0042] Example 3: Preparation of MXene@PDA / Cu NPs (50:50) composite material
[0043] This embodiment is substantially the same as embodiment 1, except that the reduction reaction temperature is 50°C.
[0044] Comparative Example 4: Preparation of MXene@PDA / Cu NPs (50:50) composite material
[0045] This embodiment is substantially the same as embodiment 1, except that the reduction reaction temperature is 80°C.
[0046] Comparative Example 5: Preparation of MXene@PDA / Cu NPs (50:50) composite material
[0047] This embodiment is substantially the same as embodiment 1, except that the reduction reaction temperature is 70°C.
[0048] Comparative Example 6: Preparation of MXene@PDA / Cu NPs (50:50) composite material
[0049] This embodiment is substantially the same as embodiment 1, except that the reduction reaction temperature is 40°C.
[0050] Example 4: Preparation of MXene / Cu NPs (50:50) composite material
[0051] (1) 1 g of MAX (Ti3AlC2) was slowly added to a solution containing 1.6 g of LiF and 20 mL of hydrochloric acid (9 mol·L -1 ) in a mixed solution. Stir and etch at 45°C for 24 hours. After etching, filter and place in 30mL of dilute hydrochloric acid solution (2mol·L -1) acid wash for 2 h. Then wash with water and ethanol three times each until the pH of the supernatant is ≥7, and place the centrifuged product in an ice-water bath for 3 h of ultrasonication. Finally, centrifuge the solution at 3500 rpm for 60 min. Collect the upper dark green dispersion and freeze-dry to obtain the two-dimensional layered material few-layer MXene.
[0052] (2) 100 mg of few-layer MXene was dispersed in 40 mL of deionized water. Then, 10 mL (0.157 mol / L) of copper nitrate and 10 mL (0.314 mol / L) of solution (the molar ratio of copper nitrate to sodium hydroxide was 1:2) and 6 mmol of reducing agent (ascorbic acid) were slowly added to the above system in a constant temperature water bath at 60 °C for reduction reaction. Finally, the reaction product was cooled, filtered, and washed to obtain a MXene / Cu NPs composite material.
[0053] Example 5: Thermal Decomposition of Ammonium Perchlorate
[0054] Take 0.7 mg of ammonium perchlorate to test TG-DSC, test conditions: heating rate of 10℃ / min, heating range of 100℃-500℃, nitrogen atmosphere, flow rate of 20mL / min. Test results are shown in Figure 3 ,DSC curve shows that the high temperature decomposition temperature of AP is 431.4℃.
[0055] Example 6: MXene@PDA / Cu NPs samples prepared with different mass ratios of MXene to Cu NPs catalyze the thermal decomposition of ammonium perchlorate
[0056] In an agate mortar, 0.01g of MXene, Cu NPs, MXene / Cu NPs, MXene@PDA / Cu NPs samples prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were added respectively, and 10mL of anhydrous ethanol was added for ultrasonic dispersion for 10 minutes. Then, 0.49g of AP was weighed and placed in a mortar, and ground while ultrasonicating until the dispersion became a paste. Finally, the mixed sample was placed in a 60°C oven and dried for 1h. After drying, about 0.7mg was taken for TG-DSC testing. Test conditions: heating rate of 10°C / min, heating range of 100°C-500°C, nitrogen atmosphere, flow rate of 20mL / min.
[0057] The test results of the thermal decomposition of ammonium perchlorate catalyzed by each catalyst are as follows: Figure 3 shown. Figure 3The DSC curves show that after adding MXene, the high-temperature decomposition temperature of AP is 409.8°C; after adding Cu NPs, the high-temperature decomposition temperature of AP is 360.3°C; after adding MXene / Cu NPs, the high-temperature decomposition temperature of AP is 327.1°C; the effect of MXene@PDA / Cu NPs (30:70) composite material on catalyzing the thermal decomposition of AP is slightly better than that of MXene / Cu NPs, and the catalytic effect of MXene@PDA / Cu NPs (50:50) composite material is the best, with a high-temperature decomposition temperature of 323.0°C, which is better than the catalytic effects of MXene material, Cu NPs, MXene@PDA / Cu NPs (30:70) and comparative examples 1 to 3.
[0058] Example 6: Thermal decomposition of ammonium perchlorate catalyzed by MXene@PDA / Cu NPs samples prepared at different reduction temperatures
[0059] In an agate mortar, 0.01g of MXene, Cu NPs, MXene / Cu NPs, Example 1, Example 3, and MXene@PDA / Cu NPs samples prepared in Comparative Examples 4 to 6 were added, and 10mL of anhydrous ethanol was added for ultrasonic dispersion for 10 minutes. Then, 0.49g of AP was weighed and placed in a mortar, and ground while ultrasonicating until the dispersion became a paste. Finally, the mixed sample was placed in a 60°C oven and dried for 1h. After drying, about 0.7mg was taken for TG-DSC testing. Test conditions: heating rate of 10°C / min, heating range of 100°C-500°C, nitrogen atmosphere, flow rate of 20mL / min.
[0060] The test results of the thermal decomposition of ammonium perchlorate catalyzed by each catalyst are as follows: Figure 4 shown. Figure 4 The DSC curves show that the MXene@PDA / Cu NPs (50:50) composite material prepared at a reduction reaction temperature of 50°C is slightly better than MXene / CuNPs, and the MXene@PDA / Cu NPs (50:50) composite material prepared at a reduction reaction temperature of 60°C has the best AP catalytic effect, with a high-temperature decomposition temperature of 323.0°C.
[0061] Figure 1 Transmission electron micrographs of MXene material (a) and MXene@PDA / Cu NPs (50:50) composite material (b) prepared in Example 1. It can be seen that the MXene flakes prepared by etching combined with ultrasonic exfoliation largely retain the initial two-dimensional shape, with an obvious lamellar structure and no stacking phenomenon. The Cu nanoparticles on the surface of the MXene@PDA / Cu NPs (50:50) composite material are well dispersed, with a particle size of about 20 nm.
[0062] Figure 2 The XRD curves are of MXene material, Cu NPs, Example 4, Examples 1 to 2, and MXene@PDA / Cu NPs composite materials of different mass ratios of Comparative Examples 1 to 3. In the MXene@PDA / Cu NPs composite material, as the content of Cu NPs increases, the peak intensity of the characteristic peak of Cu NPs in MXene@PDA / Cu NPs increases continuously and gradually covers the characteristic peak of MXene.
Claims
1. A method for preparing a MXene@PDA / Cu NPs composite material, characterized in that: The steps include: Step 1, preparation of few-layer MXene: placing the MAX material in a LiF HCl solution, stirring and etching, washing, centrifuging, peeling, and freeze-drying to obtain a two-dimensional layered material few-layer MXene; Step 2, preparation of MXene@PDA: a few layers of MXene are dispersed in Tris-HCl buffer, dopamine hydrochloride is then added, stirred to cause polymerization, washed, and dried to obtain MXene@PDA; Step 3, preparation of MXene@PDA / Cu NPs: adding MXene@PDA to water for ultrasonic dispersion, followed by adding copper nitrate, sodium hydroxide and ascorbic acid solution, and performing a reduction reaction at 50-60°C. After the reaction, the reaction product was cooled, filtered and washed to obtain a MXene@PDA / Cu NPs composite material with a mass ratio of MXene to Cu NPs of 50:50-30:
70.
2. The preparation method according to claim 1, characterized in that In step 1, the concentration of HCl solution is 9 mol∙L -1 ; In the LiF-HCl solution, the concentration of LiF is 3 mol∙L -1 .
3. The preparation method according to claim 1, characterized in that In step 1, the etching time is 24 h, the etching temperature is 45°C, and the stirring speed is 400 rpm.
4. The preparation method according to claim 1, characterized in that In step 1, the washing method is to first use 2 mol∙L -1 After washing with HCl solution, the samples were washed with water and ethanol for 3 times respectively. The pH of the supernatant after washing was ≥7.
5. The preparation method according to claim 1, characterized in that In step 1, the stripping time was 3 h, the centrifugal speed was 3500 rpm, and the centrifugal time was 60 min.
6. The preparation method according to claim 1, characterized in that In step 2, the mass ratio of the few-layer MXene to dopamine hydrochloride is 100:10, the pH of the Tris-HCl buffer is 8.5, and the polymerization reaction time is 8 h.
7. The preparation method according to claim 1, characterized in that: In step 3, the molar ratio of copper nitrate to sodium hydroxide is 1:
2.
8. The preparation method according to claim 1, characterized in that: In step 3, the reaction time is 4 h.
9. The MXene@PDA / Cu NPs composite material prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the MXene@PDA / Cu NPs composite material according to claim 9 in catalyzing the thermal decomposition of ammonium perchlorate.
Citation Information
Patent Citations
Preparation method of nano 2,4-copper resorcylic
CN104610042A
Copper complex as well as preparation method and application thereof
CN115093435A
Cited By
Ultrafiltration membrane for sewage treatment and preparation method thereof
CN121401877A